O direito à moradia adequada através dos instrumentos urbanísticos de regularização fundiária, a partir da Lei nº 11.977/2009 - Daud, Samira dos Santos (2015)
This study aims to analyze the right to adequate housing, through the urban instruments of land regularization of social interest, such as the urban demarcation, the legitimacy of ownership and administrative adverse possession, created by Law No. 11,977 / 2009, as a way extrajudicial solution of urban land conflicts. This is on the problem of illegal occupation of land in cities, irregular, illegal and illegal settlements and the lack of legal regulation of ownership, rapid urbanization in this context that prevents the exercise of the right to adequate housing. The problem stems from the rapid and unplanned growth of cities, from the beginning of the industrialization process, with the rural exodus that, to meet the intense labor recruitment, fostered the cluttered appearance of settlements without housing in large cities . The development and expansion of cities in Brazil occurred without any control or predetermined orientation, despite being the municipality the legal entity of public law responsible for the use and occupation of land, as advocated in the articles 182 and 183 of the Federal Constitution, which establish the guidelines of the national urban policy. The 1988 Constitution, in Article 1, has among the reasons the dignity of the human person, the social values of work and free enterprise, and has the fundamental right of item XXII of Article 5, the right to property, corollary of the right to free enterprise, which should meet the social function. As the housing is directly related to the dignity of the human person, the Constitution busied grant ownership to those using urban property to house his and his family, in accordance with art. 183, requiring the property an obligation to fulfill a social purpose, especially for citizens of lower economic potential, so that both the Constitution and the laws aimed infra grant these citizens the right to housing, even without property, and a second time, consolidate both rights, housing and property through legal and administrative instruments in favor of the citizen. Search will be conceptualizing the possession and ownership, as well as housing, housing in this context the right to the city and the urbanization process, and identify the objectives and purposes of land tenure in Brazil, mainly from the Law No. 11,977 / 2009 with the changes introduced by Law No. 12,424 / 2011, analyzing the urban instruments of urban land regularization of social interest created with the new legislation, to ensure effectiveness of the fundamental right to housing, showing up mainly that administrative prescription is one way of consolidating these rights.